Cytochrome P450 CYP76F14 Mediates the Conversion of Its Substrate Linalool in Table Grape Berries - Zhizhong Song; Jinjin Zhang; Matthew Shi; Dong Li; Xiaohua Liu (Horticulturae)
Aroma composition serves as a pivotal quality determinant in table grapes (Vitis vinifera). While the cytochrome P450 enzyme CYP76F14 is implicated in aroma biosynthesis, its functional role in grape berries remains uncharacterized. A comparative analysis of three aroma-distinct cultivars—Muscat type ‘Irsai Oliver’, Neutral type ‘Yanhong’, and Berry-like type ‘Venus Seedless’—revealed cultivar-specific linalool accumulation patterns. ‘Irsai Oliver’ exhibited sustained linalool biosynthesis from the fruit set through to maturity (from Stage 1 to Stage 5), with concentrations peaking at Stage 3 (veraison phase) and remaining elevated until harvest, surpassing the other two cultivars. Transcriptional profiling demonstrated that the CYP76F14 expression exhibited a similar trend with the accumulation of linalool levels, showing a higher expression in ‘Irsai Oliver’ across the developmental stages. A structural analysis identified 12 divergent residues in the ‘Irsai Oliver’ CYP76F14 variant, including E378 and T380 within the conserved substrate recognition site. The site-directed mutagenesis of these residues (CYP76F14-E378G/T380A) reduced the catalytic efficiency by 68–72% compared to the wild-type (in vitro LC-MS/MS assays), confirming their functional significance. This work reveals that cytochrome P450 CYP76F14 mediates the conversion of its substrate linalool in table grape berries, especially of Muscat type grapes, and proposes the CYP76F14 polymorphic variants as molecular markers for aroma-type breeding. The identified catalytic residues (E378/T380) provide targets for enzymatic engineering to modulate the terpenoid profiles in Vitis species.